Mussolini meets Marshall in the city - Corrado Andini; Monica Andini (Regional Studies, Regional Science, 2023)
ABSTRACTWe estimate the link between population density and labour productivity at the city level. An exogenous change in the agglomeration of some cities that occurred in Italy during the fascist dictatorship allows us to instrument the agglomeration proxy. We find evidence of a causal impact of density on productivity for the subpopulation of cities affected by the instrument. The estimated elasticity in our preferred specification is 0.252.